URGENSI HARMONISASI HUKUM PENGELOLAAN PERTAMBANGAN MINYAK DAN GAS BUMI LEPAS PANTAI DI ERA OTONOMI DAERAH - Heriyandi Heriyandi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The management of off shore gas and oil mining in regional autonomy era is related to three categories of law regulations, namely the categories of regulations on mining, marine area and regional autonomy. Each regulation can reach its goals if one another works harmoniously, however, in reality these three categories of regulations are disharmonious, either in the principles of the objectives, institution authority, or law implementation area. Therefore, this paper will explain the importance of harmonization and the substance of regulations needed to harmonize.